Apios americana Medik leaf extracts attenuate H2O2-induced hepatotoxicity. (June 2021) - Chu, Qiang; Jia, Ruoyi; Chen, Chaowei; Wang, Yaxuan; Yu, Xin; Zhang, Yiru; Wu, Tao; Zheng, Xiaodong
Abstract: Apios americana Medik leaves are rich in polyphenols and prevent glucose-induced damage in organisms. Polyphenols are a group of natural antioxidants. Therefore, a H2 O2 induced oxidative stress model of HepG2 cells was used to explore the protective effects of the Apios americana Medik leaves water extract (ALWE) against oxidative stress. Nine compounds were identified in ALWE using HPLC-TOF-MS including C18 H24 O13, which had not previously been reported. Fluorescence staining assays showed that the ALWE significantly decreased apoptosis, intracellular ROS generation, mitochondrial membrane potential (MMP) dissipation and mitochondrial membrane lipid peroxidation after ALWE pretreatment. Data from western blots showed that Keap1-Nrf2 and Sirt1-FoxO1 signaling pathways were involved in preventing H2 O2 induced oxidative stress. Transmission electron microscope and Western blot analyses indicated that autophagy contributed to the regulation of the oxidative balance. These results together indicated that ALWE is a potential antioxidant and autophagy activator, and it protects HepG2 cells against H2 O2 damage through activation of autophagy.